2022
DOI: 10.1051/0004-6361/202142296
|View full text |Cite
|
Sign up to set email alerts
|

Missing large-angle correlations versus even-odd point-parity imbalance in the cosmic microwave background

Abstract: Context. The existence of a maximum correlation angle (θ max 60 • ) in the two-point angular temperature correlations of cosmic microwave background (CMB) radiation, measured by WMAP and Planck, stands in sharp contrast to the prediction of standard inflationary cosmology, in which the correlations should extend across the full sky (i.e., 180 • ). The introduction of a hard lower cutoff (k min ) in the primordial power spectrum, however, leads naturally to the existence of θ max . Among other cosmological anom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…[7] The most recent analysis of the Planck data shows that a likely reason for this large-scale anomaly is a hard cutoff, k min = 4.34 ± 0.50∕r cmb , where r cmb is the comoving distance to the surface of last scattering, in the (scalar) fluctuation power spectrum P s (k). [10][11][12] Generic inflation would instead be consistent with an essentially zero k min which, however, is ruled out at over 8𝜎 by these data. Such a spectral cutoff is not easy to accommodate with an inflationary scalar field because k min would signal the first mode crossing the Hubble horizon and freezing during the quasi-de Sitter expansion, [13] establishing the time at which inflation started.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…[7] The most recent analysis of the Planck data shows that a likely reason for this large-scale anomaly is a hard cutoff, k min = 4.34 ± 0.50∕r cmb , where r cmb is the comoving distance to the surface of last scattering, in the (scalar) fluctuation power spectrum P s (k). [10][11][12] Generic inflation would instead be consistent with an essentially zero k min which, however, is ruled out at over 8𝜎 by these data. Such a spectral cutoff is not easy to accommodate with an inflationary scalar field because k min would signal the first mode crossing the Hubble horizon and freezing during the quasi-de Sitter expansion, [13] establishing the time at which inflation started.…”
Section: Introductionmentioning
confidence: 77%
“…Both of these anomalies are eliminated by the use of a power spectrum, P s (k), with the aforementioned cutoff, k min . [10,12] The fact that both of the empirically derived anomalies can be accounted for with the same feature in P s (k), i.e., k min , adds weight to the reality of such a cutoff. Actually, it appears that an odd-even parity imbalance is also required to optimize the fit to the Planck-2018 data.…”
Section: The Numen Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…An in-depth analysis of the latest Planck data focusing on this particular issue (Melia & Lopez-Corredoira 2018;Melia et al 2021;Sanchis-Lozano et al 2022) has shown that the paucity of large-angle correlations is best explained by the presence of a cutoff,…”
Section: Angular Size Of the Largest Mode In The Cmb Fluctuationsmentioning
confidence: 99%
“…This outcome is highly relevant to our identification of where the anisotropies in the CMB were produced because it provides an entirely new length scale (i.e., l max ) one may use to estimate z dust . The optimization that completely removes the angular correlation anomaly is given as =  u 4.34 0.50 min , where º u k r min min dust in terms of the comoving radius (r dust ) to the dust screen (Melia & Lopez-Corredoira 2018;Sanchis-Lozano et al 2022). It is easy to see that one may therefore write…”
Section: Angular Size Of the Largest Mode In The Cmb Fluctuationsmentioning
confidence: 99%